Purchase and Utilization of New Fuel Efficient Vehicles in the US: Evidence from the 2009 National Household Transportation Survey Data - Su, Qing (International Journal of Energy Economics and Policy, 2013)
This paper applies a simultaneous equation model to examine the relationship between choices of new fuel efficient vehicles and their utilization using the 2009 NHTS data. The regression results indicate that travelers purchasing new fuel efficient vehicles with a fuel economy of at least 30 mpg drive more on a monthly basis than others owning a new vehicle with lower fuel economy. In addition, those who travel more are more likely to purchase a new fuel efficient vehicle with a fuel economy of at least 30 mpg in the study period. The gasoline price has a significant negative impact on new vehicle utilization while a significant positive impact on choices of new vehicles with a fuel economy of at least 30 mpg. Keywords: new fuel efficient vehicle; new vehicle utilization; simultaneous equation model; impact of gasoline prices; vehicle type choice JEL Classifications: R22; R41